Semax intranasal improve memory deficiency in conditions of experimental chronic brain ischemia - Kirchev, V. (Journal of Education, Health and Sport, 2024)
Statistical indexes of the incidence of acute cerebrovascular accidents in our country highlight the negative dynamics of the progressive increase in the number of new cases of strokes. It is interesting, promising and expedient to clarify the effectiveness of endonasal administration of the peptide drug Semax in the dynamics of the post-ischemic period from the point of view of the potential restoration of impaired mnestic functions. The purpose of the work was the determination of the effectiveness of endonasal administration of Semax in restoring memory impairment in rats in the dynamics of the post-ischemic period. A model of chronic brain ischemia was reproduced by isolating and bilaterally ligating the carotid arteries. Rats with chronic brain ischemia were administered Semax endonasally. The rats were observed for 7 days, during which the animals were examined for mnestic functions under the conditions of formation of a conditioned active avoidance reflex and a conditioned food reflex. The obtained data indicate the formation of pronounced mnemic dysfunctions in the dynamics of the postischemic period, which are characterized by a deterioration in the learning process, as well as a pronounced suppression of short- and long-term memory under the conditions of the conditioned reflex of active avoidance, which is combined with violations of the processes of learning, preservation and extinction of the food conditioned reflex. The noted amnestic effects are persistent, are registered in rats already 24 hrs after bilateral occlusion of the carotid arteries and continue throughout the experiment. Considering the mechanisms of implementation of the neuroprotective effect of Semax and the endonasal route of its administration, the authors consider it appropriate and pathogenetically justified to include Semax in a comprehensive scheme of pharmacological correction of cognitive disorders or prevention of their development in cerebrovascular pathology.